Mitologia em Schelling: apresentação do conceito de mitologia através da investigação das obras Filosofia da mitologia e Filosofia da arte - Goes, Vitor Luis Carvalho de (2019)
Mythology, a complex and embracing concept, with a multiplicity of meanings depending on the context in which each one appears, is one of the objects of the philosophical inquiry of Friedrich Wilhelm Joseph Schelling, the thinker studied in this dissertation. Mythology, for Schelling, is the Universe itself, in its higher resemblance, in its supreme reality, as it is in the Absolute, which can only be figured through fantasy, transcendental faculty used by poets and artists to access the realm of the Gods. The philosophical inquiry undertaken by Schelling not only reveals the aesthetic dimensions of mythology, but its metaphysical and religious dimension as a whole. Mythology is grounded in a theogonic process in which actual living, and active, Divine potencies, succeed one upon another inside the human consciousness that once was in the Godhead, leaving remnants of histories and doctrines of the gods. Through a carefully work, here where analyzed the main works of the philosopher, that approach this matter, Philosophy of Art and Philosophy of Mythology, with the intent to present the concept of mythology in each one of Schelling’s philosophy moments, emphasizing, justifiably, his latter philosophy, approaching also, the possibility of a philosophical religion